Histopathological diagnosis of dermatological lesions: a Hospital-based study - Upadhyaya Kafle, Santosh; Yamu, Sabrina (Journal of Karnali Academy of Health Sciences, 2021)
Introduction: The skin is susceptible to a wide range of pathological conditions. The histopathological analysis is mandatory for the accurate diagnosis of many of these conditions. Sometimes, additional recommendations and ancillary techniques are required for its confirmation and further classification. The study aims to analyze the various ancillary techniques and recommendations status made during the histopathological diagnosis of dermatological lesions. Methods: This cross-sectional observational study was conducted for all skin biopsies (n=129) received from January 2017 to June 2020 at the Department of Pathology, Birat Medical College Teaching Hospital, Morang, Nepal. H&E stained slides of these biopsies were retrieved from the departmental archives and reviewed under light microscopy for the diagnoses made before. The various ancillary techniques and recommendations status made during diagnosis along with its correlation between categorization of histopathological diagnoses was analyzed using SPSS version 17. Results: Among 129 skin biopsies, various recommendations and ancillary technique status were 102(79.06%) and 78(60.46%) respectively. Among which, “special stains” and “follow up biopsy after adequate medication” status was maximum with 65(50.4%) cases each. Likewise, the “more representative biopsy” in 03 (2.3%) cases, “immunofluorescence study” and “special stain and immunohistochemistry panel study” each in 01(0.8%) cases were seen among the rare ones respectively. Infectious lesions of bacterial origin in 32 (24.8%) cases, of fungal and viral origin each in 02(1.6%) cases were the most common and rare diagnosis respectively. The categorization of histopathological diagnosis revealed significant association (p≤0.001) with various recommendations and ancillary techniques status. Conclusion: The significant correlation among various ancillary techniques and recommendations status made during histopathological diagnoses of dermatological lesions reflected its importance in diagnosing dermatological lesions.